Manajemen SDM Berbasis Nilai Islami di Madrasah Ibtidaiyah: Studi Kualitatif di MI Matlaul Atfal - Shinta Meirnawati Pratiwi Putri; Mulyawan Safwandy Nugraha (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study aims to analyze the handling of human resource (HR) issues at Madrasah Ibtidaiyah Matlaul Atfal based on Islamic values within the framework of Islamic Education Management. The study is motivated by the limited number of empirical studies examining the operational implementation of Islamic values in human resource management at the Islamic primary school level. This research employed a mini research design using a descriptive qualitative approach. The research participants consisted of nine individuals, including the principal, teachers, administrative staff, and foundation board members. Data were collected through semi-structured interviews, non-participant observation, and document analysis of seven institutional documents. Data analysis was conducted thematically through data reduction, data display, and conclusion drawing, supported by source and technique triangulation. The findings indicate that the integration of Islamic values such as amanah (trustworthiness), ihsan (excellence), justice, deliberation (shura), and sincerity (ikhlas) in human resource planning, recruitment, training, performance evaluation, and character development contributes positively to improving professional competence, work ethics, and motivation among teachers and staff. Furthermore, the application of Islamic values strengthens the Islamic school culture and helps minimize internal conflicts. This study provides a theoretical contribution by reinforcing the empirical model of Islamic value-based human resource management in Islamic primary schools and a practical contribution as a reference for sustainable and character-based human resource management policies KEYWORDS: Human Resource Management; Human Resources; Islamic Education Management; Islamic Primary School; Islamic Values Abstrak Penelitian ini bertujuan menganalisis penanganan isu sumber daya manusia (SDM) di Madrasah Ibtidaiyah Matlaul Atfal berbasis nilai Islami dalam kerangka Manajemen Pendidikan Islam (MPI). Studi ini dilatarbelakangi oleh keterbatasan penelitian empiris yang mengkaji implementasi operasional nilai-nilai Islami dalam manajemen SDM pada jenjang madrasah ibtidaiyah. Penelitian menggunakan metode mini research dengan pendekatan kualitatif deskriptif. Subjek penelitian berjumlah sembilan partisipan yang terdiri atas kepala madrasah, guru, tenaga administrasi, dan pengurus yayasan. Data dikumpulkan melalui wawancara semi-terstruktur, observasi non-partisipan, serta studi dokumentasi terhadap tujuh dokumen kelembagaan. Analisis data dilakukan secara tematik melalui tahapan reduksi data, penyajian data, dan penarikan kesimpulan dengan menerapkan triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa integrasi nilai Islami seperti amanah, ihsan, keadilan, musyawarah, dan ikhlas dalam perencanaan SDM, rekrutmen, pelatihan, evaluasi kinerja, serta pembinaan karakter SDM berkontribusi positif terhadap peningkatan kompetensi profesional, etika kerja, dan motivasi guru serta tenaga kependidikan. Selain itu, penerapan nilai-nilai Islami tersebut turut memperkuat budaya kerja madrasah yang harmonis dan religius serta meminimalkan potensi konflik internal. Penelitian ini memberikan kontribusi teoretis dalam memperkaya kajian empiris mengenai manajemen SDM berbasis nilai Islami pada madrasah ibtidaiyah serta kontribusi praktis sebagai rujukan kebijakan pengelolaan SDM yang berkelanjutan dan berkarakter Islami. KATA KUNCI: Madrasah Ibtidaiyah; Manajemen Pendidikan Islam; Manajemen SDM; Nilai Islami; Sumber Daya Manusia